Kappa Test with Platelet Rich Plasma and Platelet Poor Plasma Blood Preparation Method for Examining The Value of Activated Partial Tromboplastin Time and Plasma Protrombin Time - Ratih Hardisari; Supartuti Supartuti (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2016)
Examining the Activated Partial Thromboplastin (APTT) and Plasma Prothrombin Time (PPT) is sort series of examining homeostasis which is conducted in order to have a screening test for homeostasis disorder. This examination used plasma sample in which there were solidification factors which could be influenced by thrombocyte existence. The centrifuging of citrate blood sample which was conducted too fast or too slow would cause plasma condition with the number of thrombocyte. Practical in some laboratories were not yet been uniformed, mainly in centrifuging of citrate blood to obtain citrate plasma with less thrombocyte contents. To identify the value of Kappa by compatibility test between two methods PRP and PPP to examine PPT and APTT. This experiment is a true experiment with post-test research design without control. Citrate plasma sample was obtained from 10 sample of students' blood which had one pair, 2 treatments; by centrifuging 3000 rpm for 10 minutes for PPP and centrifuging 1000 rpm for 10 minutes for PRP. Then, both methods (PPP and PRP) were examined by using PPT and APTT parameter. In the result of PPT examination in the sample of PRP plasma, the average value was 11.6 seconds. In the sample of PPP, the average value was 11.0 seconds. The result of APTT examination in PRP sample, the average value was 34.27 seconds while in PPP sample was 33.18 seconds. There was compatibility in the result, either PPP method and PRP for PPT and APTT examination (Kappa = 1).